The Effect of Self-Efficacy and Obedience Pressure on Audit Judgment Using Task Complexity and Moral Reasoning as Moderating Variables - Putri, Ni Wayan Yundari; Latrini, Made Yenni (E-Jurnal Akuntansi; Vol 34 No 9 (2024), 2024)
This study investigates the influence of self-efficacy, obedience pressure, and task complexity on audit judgment. The research was conducted at the BPK RI Representative Office in Bali Province, with a sample of 51 auditors selected through purposive sampling. To assess the effects of the independent variables on audit judgment, multiple linear regression analysis was employed. The results demonstrate that self-efficacy positively and significantly affects audit judgment, while both obedience pressure and task complexity have significant negative impacts. These findings contribute to the theoretical development of attribution theory and offer valuable insights for various stakeholders in the field.